2022
DOI: 10.3389/fimmu.2022.951247
|View full text |Cite
|
Sign up to set email alerts
|

CXCL11 Correlates with Immune Infiltration and Impacts Patient Immunotherapy Efficacy: A Pan-Cancer Analysis

Abstract: BackgroundImmunotherapy has achieved great success in cancer. Nevertheless, many patients cannot benefit from immune checkpoint blockade therapy because of the scantiness of CD8+ T cell infiltration in the tumor microenvironment (TME). CXCL11 is known as a regulator that influences T-cell infiltration into tumors. However, the role of CXCL11 in pan-cancer is still unclear.MethodsIn this study, we investigated the expression and function of CXCL11 across 33 types of cancers based on datasets from The Cancer Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…5e, most chemokines in CDC42 gene set mutation patients were significantly higher than in CDC42 gene set wild type patients. Previous studies have reported that CXCL9, CXCL10 and CXCL11 can enhance T cell infiltration, thereby improving the therapeutic efficacy of ICI interventions[4749]. The expression of CXCL13 can generate effector T cells and is closely associated with the response to ICIs treatment[50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5e, most chemokines in CDC42 gene set mutation patients were significantly higher than in CDC42 gene set wild type patients. Previous studies have reported that CXCL9, CXCL10 and CXCL11 can enhance T cell infiltration, thereby improving the therapeutic efficacy of ICI interventions[4749]. The expression of CXCL13 can generate effector T cells and is closely associated with the response to ICIs treatment[50].…”
Section: Resultsmentioning
confidence: 99%
“…In TME, leukocyte fraction, lymphocyte fraction, TIL fraction and CD8 T cell levels were substantially higher in patients with CDC42 gene set mutations compared to those with CDC42 gene set wild type, indicating enhanced immunity. The increased expression of chemokines, such as CXCL9, CXCL10 and CXCL11, in patients with CDC42 gene set mutations can recruit more T cells into TME [47][48][49]. Additionally, higher expression of interleukins, like IL-10 and IL-21, in CDC42 gene set mutation patients promotes the survival of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the role of chemokines in the progression of LUAD is crucial, suggesting their potential importance in disease development. Multiple studies have indicated that the expression of members of the chemokine family is associated with poor prognosis in LUAD 60–62 . Indeed, the GSEA results suggest that patients in the high‐risk group have a poorer survival prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We used UALCAN, an interactive web resource ( http://ualcan.path.uab.edu/index.html ) which provides cancer OMICS data, including TCGA (The Cancer Genome Atlas) [ 22 ] and MET500 database [ 23 ], to screen the top 50 overexpressed genes and to analyze the expression of YKL-40 (CHI3L1) in STAD patients. TIMER (Tumor Immune Estimation Resource) [ 24 ] ( https://cistrome.shinyapps.io/timer ) provides survival module between gene expression and clinical outcome in a multivariable Cox proportional hazard model, and has the functions to draw Spearman's correlation curves and to provide pair-wise gene expression correlation analysis for given sets of TCGA and/or GTEx (the Genotype-Tissue Expression) database [ 25 ]. Using TIMER, we performed the correlation analysis between ADRB genes (ADRB1, ADRB2, and ADRB3) and CHI3L1, and analyzed the correlations of NGF expression and macrophage infiltration with the cumulative survival rate.…”
Section: Methodsmentioning
confidence: 99%